Far-right violence as backlash against gender equality: A county-level analysis of structural and ideological gender inequality and homicides committed by far-right extremists - Mills, Colleen E. (Journal of crime and justice, 2020)
In the aftermath of the far-right rally in Charlottesville that led to the murder of counter-protester Heather Heyer in August 2017, attention turned to the reaction by extremists on far-right websites and their vitriolic language against Heyer. Such rhetoric evidenced the intertwined nature of white supremacy and misogyny. The modern far-right movement grew in reaction to social changes such as greater equality across gender and racial lines. Feminist perspectives on male violence offer competing hypotheses where greater gender inequality may lead to less (backlash) or greater (ameliorative) violence. The current study uses data on homicides committed by far-right extremists from the United States Extremist Crime Database (ECDB) to assess far-right violence as an outcome of gender inequality. Results show that counties with greater gender inequality, in favor of men, in occupation and income, experience a decrease in the odds of a far-right homicide occurring. Once a far-right homicide occurs, gender inequality in occupation has a further pacifying effect as greater inequality is associated with a decline in far-right violence. Taken together, these findings provide support for the backlash hypothesis as they demonstrate that greater gender equality is associated with far-right violence.